Development and optimisation of three-dimensional freeze-dried collagen-based scaffolds - Xue, B; Bin Xue (2014)
Three-dimensional collagen/chitosan scaffolds fabricated by freeze-drying technique in 96-well polystyrene and PDMS plates were optimized during this study. Surface tension is, by and large, one of the most limiting factors in fabricating freeze-dried scaffolds in small format well plates. Traditionally, bowl-shaped top surfaces of collagen/chitosan scaffolds were common in polystyrene 96-well plate; whereas for PDMS 96-well plate, dome-shaped surfaces were formed. These surface tension phenomena are not desirable in cell studies especially during initial cell seeding. A combination of surface treatment and change of freeze-drying regime were developed to mitigate the surface tension problem in PS and PDMS 96-well plates respectively. Collagen/chitosan scaffolds of varying concentration and composition were experimented in both polystyrene and PDMS 96-well plates. Thin water film treatment with UV cross-linking was successfully used to eliminate meniscus in PS well plates; pre-cooling, on the other hand, was utilised to treat scaffold solutions in PDMS well plates. The resultant matrices all had flat top surfaces and average thickness of 1 mm. As expected, scaffolds with lower overall polymer concentration or, from a compositional perspective, scaffolds with high chitosan content generally had larger pores. Microscopic observation by multi-photon microscope was performed and chemical analyses were conducted to characterize the surface-treated scaffolds. In addition, scaffolds were tested in vitro using DLD-1 cells, hMSCs and fibroblasts for their biological performance. The purpose of this study was to address the problem of using small format culture wells for the fabrication of freeze-dried collagen-based scaffolds for studies of cell growth in 3D culture and in microfluidic perfusion bioreactors.